Use of a Spline Function of a Fractional Degree for the Description of the Base Line in the Determination of Platinum by Stripping Voltammetry; Journal of Analytical Chemistry; Vol. 56, iss. 1 - Romanenko S. V. Sergey Vladimirovich (2001, 2001)
The systematic error in measuring the analytical signal of Pt obtained at a mercury thin-film electrode with staircase potential sweep has been studied. The description of the residual current by splines of degree 2.5 reduces the average systematic error by the factor of 4.3 as compared to the linear description. It is shown that splines of degree 2.5 are more stable as compared to the cubic splines, which suggests that the random error arising from the subtraction of the residual current is reduced when the spline degree decreases from 3 to 2.5.